Static and dynamic oxidation behaviour of silicon carbide at high temperature. Issue 11 (September 2021) - Chen, Shiyan; Zeng, Yi; Xiong, Xiang; Lun, Huilin; Ye, Ziming; Jiang, Tianxing; Yang, Lingwei; Zhang, Jun; Liu, Liping; Wang, Guolin; Jing, Li; Xie, Xiangqian; et al.
Highlights: The static and dynamic oxidation of SiC were investigated in air and in plasma wind tunnels, respectively. The activation energies for static oxidation were approximately ten times higher than the value of dynamic oxidation. The observed Si-O-C transition layer located at the SiO2 /SiC interface after both static and dynamic oxidation. Abstract: SiC has extensive applications in high-temperature oxidation environments. However, few studies have investigated the differences between the static and dynamic oxidation behaviour. In this study, the static and dynamic oxidation of SiC were investigated in air and in plasma wind tunnels, respectively. The results demonstrated that the activation energy of static oxidation was ∼68.02 kJ/mol at 1300–1600 ℃, which was approximately ten times that of dynamic oxidation ∼7.05 kJ/mol at 1290–1534 ℃. The observed Si-O-C transition layer located at the SiO2 /SiC interface, and its thickness after dynamic oxidation for 300 s was thicker than that after static oxidation for 30 h. In dynamic oxidation, high-speed flowing atomic oxygen reacted directly with SiC, whereas molecular oxygen needed extra energy to break the OO bond and react with SiC in static oxidation. Atomic oxygen also migrated easier in the amorphous SiO2 coating, contributing to a thicker Si-O-C layer and lower activation energy.